ANALYSIS OF THE ENERGY CHARACTERISTICS OF THE RESIDENTIAL HOUSE TAKING INTO SOCIAL AND EXPLOITATIVE FACTORS - ШОВКАЛЮК, М. М.; ПАХУНОВА, К. Ю.; ШЕВЧЕНКО, О. М. (Technologies and Engineering, 2023)
Introduction. In view of the energy dependence of Ukraine, improving the energy efficiency of the housing stock is an extremely urgent task. The building is a complex energy system, for the study of which a systematic approach is used; therefore, the methods of energy modeling using software systems become relevant. Purpose. Conducting an energy survey with a survey of residents and determining energy characteristics using software products for energy auditors for modeling and equipment selection. Methodology. The study included instrumental measurements, a feasibility study using engineering calculation methods, a survey of residents, modeling in specialized software products RETScreen, DesignBuilder, Audytor OZC, PV-SOL and T-SOL; the integrated cost method was used to select the heat source. Findings. The structure of energy consumption of the building was obtained and an assessment of the energy saving potential was carried out, taking into account the features of operation and technical capabilities; three packages of energy-saving measures have been proposed. Using the developed models in specialized programs, modeling of energy consumption before and after the implementation of measures was carried out and equipment for the use of solar energy was selected. The study was carried out as part of the work on a master's thesis. Originality. The possibilities of different software for modeling the energy characteristics of a 7residential building are considered, a comparative analysis of the results and the choice of one of the measures based on cash flow analysis Practical value. With the help of the software, 3D models were built and applied studies of energy characteristics were carried out and proposals were developed for the thermal modernization of an existing residential building, taking into account the actual operating conditions, three packages of measures “Minimum”, “Optimal”, “Maximum” were proposed.